The roles and clinical applications of interleukins in endometrial carcinoma - Zang, Yuqin; Li, Huanrong; Liu, Shiqi; Zhao, Ruqian; Zhang, Kaiwen; Zang, Yuqi; Wang, Yingmei; Xue, Fengxia (Frontiers in Oncology, 2022)
As a common malignant tumor of the female reproductive system, endometrial carcinoma (EC) seriously endangers women’s health with an increasing incidence. The oncogenesis and progression of cancer are closely linked with immune microenvironment, of which interleukins are the important components. In order to illustrate the roles and clinical applications of interleukins in EC, literature of interleukins and EC were reviewed. Based on the present studies, interleukins play crucial roles in the oncogenesis and development of EC via regulating the proliferation, migration, invasion, angiogenesis, apoptosis, pyroptosis and autophagy of EC as well as the immune function against EC. And some of the interleukins seems to have prospective clinical applications in EC, such as evaluating the risk of tumorigenesis, discriminating the malignancy from benign disorders or normal condition, indicating cancer aggressiveness, predicting the prognosis of patients and serving as the novel therapy. However, there is still a long way to go before the clinical applications of interleukins in EC come into reality. Nevertheless, it is certain that the exploration of interleukins will definitely be of great benefit to the screening, diagnosis and treatment of EC in the future.